Decarbonising Rotterdam?: Energy transitions and the alignment of urban and infrastructural temporalities. Issue 4 (3rd September 2019) - Elsner, Ivonne; Monstadt, Jochen; Raven, Rob
Abstract : Low carbon transitions of urban energy systems have been on urban research and policy agendas for several years now. While the spatialities of infrastructure transitions have been widely discussed, their temporalities have attracted much less attention. This is surprising, since the transition of urban infrastructures in the course of system integration and decarbonisation reveal strong temporal dynamics: new temporalities or temporal requirements not only emerge as a result of technological change (e.g. by integrating fluctuating renewables or storage technologies) but also of changing social practices (e.g. in urban load management or energy use). We argue that aligning urban and infrastructure temporalities involves negotiations between the various energy providers, regulators and users involved and is a highly political process. As we know little about such temporal dynamics so far, this study uses an explorative methodology to elaborate on a conceptual framework of urban and infrastructural temporalities. This framework has been developed in an iterative way by going back and forth between conceptual contributions and empirical findings drawn from expert interviews regarding low carbon transitions in Rotterdam. Our case study of Rotterdam indicates that unsolved challenges in aligning urban and infrastructural temporalities can be seen as a major restriction to realise low carbon energy solutions.